2004
DOI: 10.1021/bi049270a
|View full text |Cite
|
Sign up to set email alerts
|

Topology Scanning and Putative Three-Dimensional Structure of the Extracellular Binding Domains of the Apical Sodium-Dependent Bile Acid Transporter (SLC10A2)

Abstract: The apical sodium-dependent bile acid transporter (ASBT, SLC10A2) facilitates the enterohepatic circulation of bile salts and plays a key role in cholesterol metabolism. The membrane topology of ASBT was initially scanned using a consensus topography analysis that predominantly predicts a seven transmembrane (TM) domain configuration adhering to the "positive inside" rule. Membrane topology was further evaluated and confirmed by N-glycosylation-scanning mutagenesis, as reporter sites inserted in the putative e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
114
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(123 citation statements)
references
References 35 publications
9
114
0
Order By: Relevance
“…However, there is still controversy about the exact number of transmembrane helices. Using N-glycosylation-scanning mutagenesis, Zhang and coworkers strongly suggested a model with seven transmembrane domains for human ASBT (Zhang et al 2004). In contrast, a nine-transmembrane domain arrangement was found by Hallén and coworkers for human ASBT and NTCP (Hallén et al 1999(Hallén et al , 2000(Hallén et al , 2002b.…”
Section: Functional Properties and Expression Patterns Of The Individmentioning
confidence: 99%
See 4 more Smart Citations
“…However, there is still controversy about the exact number of transmembrane helices. Using N-glycosylation-scanning mutagenesis, Zhang and coworkers strongly suggested a model with seven transmembrane domains for human ASBT (Zhang et al 2004). In contrast, a nine-transmembrane domain arrangement was found by Hallén and coworkers for human ASBT and NTCP (Hallén et al 1999(Hallén et al , 2000(Hallén et al , 2002b.…”
Section: Functional Properties and Expression Patterns Of The Individmentioning
confidence: 99%
“…Membrane insertion and sorting of NTCP and ASBT Based on bioinformatic predictions and experimental data, it has been shown that NTCP and ASBT have an extracellular N-terminus, an odd number of transmembrane helices (seven or nine) and a cytoplasmic Cterminus (Hagenbuch et al 1991;Hagenbuch and Meier 1994;Stieger et al 1994;Dawson and Oelkers 1995;Hallén et al 1999;Hallén et al 2002b;Zhang et al 2004). Several potential N-glycosylation sites are present in NTCP, ASBT and SOAT proteins, and site-directed mutagenesis has revealed that only N 5 and N 11 in rat Ntcp (Hagenbuch 1997), and N 10 in human ASBT (Zhang et al 2004) are glycosylated.…”
Section: Functional Properties and Expression Patterns Of The Individmentioning
confidence: 99%
See 3 more Smart Citations